Effect of Mosapride Citrate Hydrate on the Colon Cleansing Action of Polyethylene Glycol Electrolyte Lavage Solution (PEG-ELS) in Guinea Pigs - Yukiko Mine; Kazuo Morikage; Seiko Oku; Takashi Yoshikawa; Isao Shimizu; Naoyuki Yoshida (Elsevier, 2009)
Abstract.: Polyethylene glycol electrolyte lavage solution (PEG-ELS) is widely used for colon cleansing prior to colonoscopy and colonic surgery. It has recently been shown that coadministration of PEG-ELS and mosapride citrate hydrate (mosapride), a selective 5-HT4-receptor agonist, is clinically useful for barium enema examination as it allows adequate barium coating. However, there is no report showing that mosapride has beneficial effects on colon cleansing and its underlying mechanism in experimental animals. In the present study, we investigated the effects of mosapride on colonic transit and on the colon cleansing action of PEG-ELS in guinea pigs. Mosapride (10 - 20 mg/kg, i.g.) significantly enhanced colonic transit rate in guinea pigs. Although PEG-ELS alone showed adequate colon cleansing action, excess fluid remained in the colon. Coadministration of mosapride (20 mg/kg) and PEG-ELS, regardless of mosapride timing, reduced colonic content weight (dry residue and water amount) as compared to PEG-ELS alone. These findings suggest that mosapride enhances the colon cleansing action of PEG-ELS via an increase in colonic transit in guinea pigs, that is, it reduces not only fecal residue but also excessive fluid in the colonic lumen. It is therefore believed that coadministration of mosapride and PEG-ELS can allow better visualization in barium enema examination. Keywords:: mosapride citrate hydrate, 5-HT4-receptor agonist, polyethylene glycol electrolyte lavage solution (PEG-ELS), colonic transit, colon cleansing